2013
DOI: 10.1016/j.jcrysgro.2012.12.176
|View full text |Cite
|
Sign up to set email alerts
|

Formation of large-grain-sized BaSi2 epitaxial layers grown on Si(111) by molecular beam epitaxy

Abstract: BaSi 2 epitaxial films were grown on Si(111) substrates by a two-step growth method including reactive deposition epitaxy (RDE) and molecular beam epitaxy (MBE). To enlarge the grain size of BaSi 2 , the Ba deposition rate and duration were varied from 0.25 to 1.0 nm/min and from 5 to 120 min during RDE, respectively. The effect of post-annealing was also investigated at 760 °C for 10 min. Plan-view transmission electron micrographs indicated that the grain size in the MBE-grown BaSi 2 was significantly increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…3(a) and 3(b)], it is found that the film grown at 64 nm/min has slightly larger grains along a planar direction (70-120 nm), while the film of 840 nm/min is elongated toward the growth direction and the planar size is 30-120 nm. These grain sizes are smaller than the domain sizes of BaSi 2 epitaxial films (>4 lm with optimized growth conditions 24,25 and 100-300 nm at higher template growth rates 7 ). By comparing the films between R ¼ 64 and 840 nm/min, one can notice that one grain sometimes covers the total depth of the film from the surface to the interface at R ¼ 840 nm/min like a columnar structure.…”
Section: B Microstructural Analysismentioning
confidence: 79%
“…3(a) and 3(b)], it is found that the film grown at 64 nm/min has slightly larger grains along a planar direction (70-120 nm), while the film of 840 nm/min is elongated toward the growth direction and the planar size is 30-120 nm. These grain sizes are smaller than the domain sizes of BaSi 2 epitaxial films (>4 lm with optimized growth conditions 24,25 and 100-300 nm at higher template growth rates 7 ). By comparing the films between R ¼ 64 and 840 nm/min, one can notice that one grain sometimes covers the total depth of the film from the surface to the interface at R ¼ 840 nm/min like a columnar structure.…”
Section: B Microstructural Analysismentioning
confidence: 79%
“…It can also be noticed that the 1=e enhancement does not accompany the increase of a in several samples such as the 890-and 2180-nm-thick films, suggesting that there is another factor influencing 1=e . Considering the previous report that the grain size of BaSi 2 is increased by annealing at 760 C in a 100-nm-thick film, 13) microstructure change such as defect elimination may also affect the carrier lifetime. However, the lifetime is degraded in such thin films by annealing, suggesting that the effect of microstructure is limited and the major factor is strain variation.…”
mentioning
confidence: 93%